Thermoelectric Power of Amorphous InAs Thin Films - Al-Maiyaly, B. K..H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The thermoelectric power (S) of thermal evaporated a-InAs filmswere measured in the temperature rang (303-408) K.These films were prepared at different thickness (250,350,450) nm and treated at different annealing temperatures (303,373,423,473,523) K.The behaviour  of the thermoelectric power  studies of these filmsas  a  function  of  thickness  and  annealing  temperature  showed  the thermoelectric  power an increasing trend with annealing temperature,whereas it decreases as the film thickness increases.